The Typology of the First Year Students’ Pronunciations At FKIP-Universitas HKBP Nommensen Pematangsiantar On English Voiceless Plosive Consonants - Bloner Sinurat; Herman Herman (Journal of English Language and Culture, 2019)
This article is regarded as a descriptive qualitative research dealing with the first year students’ skill in pronouncing the English voiceless plosive consonants. The subjects of the research are all considered homogenous consisting of 35 students who factually use Toba Batak language and Indonesian as their native languages. Based on the data analysis it was found out that those who had more phonological awareness could pronounce the English voiceless consonants better than those who had less. These speech sounds could be pronounced well when they particularly occurred either at medial or final position, but they were sometimes not properly pronounced or aspirated when they occurred in initial position and followed by stressed vowel. Phonetic errors or faulty pronunciations were more frequently done when these consonants occurred in initial position or uttered in connection with other words in a sentence.Keywords:  English, pronunciation, typology, voiceless plosive consonant